The philosophy and science of Roger Bacon
1 online resource
Keywords: "The Philosophy and Science of Roger Bacon offers new insights and research perspectives on one of the most intriguing characters of the Middle Ages, Roger Bacon. At the intersections between science and philosophy, the volume analyses central aspects of Bacon's reflections on how nature and society can be perfected. The volume dives into the intertwining of Bacon's philosophical stances on nature, substantial change, and hylomorphism with his scientific discussion of music, alchemy, and medicine. The Philosophy and Science of Roger Bacon also investigates Bacon's projects of education reform and his epistemological and theological ground maintaining that humans and God are bound by wisdom, and therefore science. Finally, the volume examines how Bacon's doctrines are related to a wider historical context, particularly in consideration of Peter John Olivi, John Pecham, Peter of Ireland, and Robert Grosseteste. The Philosophy and Science of Roger Bacon is a crucial tool for scholars and students working in the history of philosophy and science, and also for a broader audience interested in Roger Bacon and his long-lasting contribution to the history of ideas"--